European Society of Anaesthesiology and Intensive Care Guidelines on peri-operative use of ultrasound for regional anaesthesia (PERSEUS regional anesthesia): Peripheral nerves blocks and neuraxial anaesthesia. Issue 3 (12th March 2021) - Boselli, Emmanuel; Hopkins, Philip; Lamperti, Massimo; Estèbe, Jean-Pierre; Fuzier, Régis; Biasucci, Daniele G.; Disma, Nicola; Pittiruti, Mauro; Traškaitė, Vilma; Macas, Andrius; Breschan, Christian; Vailati, Davide; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Nowadays, ultrasound-guidance is commonly used in regional anaesthesia (USGRA) and to locate the spinal anatomy in neuraxial analgesia. The aim of this second guideline on the PERi-operative uSE of UltraSound (PERSEUS-RA) is to provide evidence as to which areas of regional anaesthesia the use of ultrasound guidance should be considered a gold standard or beneficial to the patient. The PERSEUS Taskforce members were asked to define relevant outcomes and rank the relative importance of outcomes following the GRADE process. Whenever the literature was not able to provide enough evidence, we decided to use the RAND method with a modified Delphi process. Whenever compared with alternative techniques, the use of USGRA is considered well tolerated and effective for some nerve blocks but there are certain areas, such as truncal blocks, where a lack of robust data precludes useful comparison. The new frontiers for further research are represented by the application of USG during epidural analgesia or spinal anaesthesia as, in these cases, the evidence for the value of the use of ultrasound is limited to the preprocedure identification of the anatomy, providing the operator with a better idea of the depth and angle of the epidural or spinal space. USGRA can be considered an essential part of the curriculum of the anaesthesiologist with a defined training and certification path. Our recommendations will require considerable changes to some training programmes, and it will be necessary for these to be phased in before compliance becomes mandatory.